Script design and advertising library leisure activities - E. V. Miroshnichenko; E. A. Beletskaja (Библиосфера)
The paper analyzes some of the organizational aspects of the leisure activities of libraries – development technology and implementation of a library script , as well as various types of its advertising and promotion. Focuses is made on the specific features of library leisure drama and certain types of advertising products, ensuring the effectiveness of library activities.